A methodology study on spent dialysate collection - SONG Jin-hui; LIU Jian-jing (Linchuang shenzangbing zazhi)
Objective To explore the accuracy of using a new kind of both simple and accurate tool to collect spent dialysate.Methods Thirty patients receiving maintenance hemo dialysis(MHD)in a stable condition were enrolled from our blood purification center.The patent method and the traditional method were used respectively to collect the spent dialysate of a whole dialysis(4 h)during the second treatment of a week.Phosphorus,urea nitrogen,creatinine and uric acid of the spent dialysate collected by two methods were determined,and the obtained data were classified as "patent group"and"traditional group".Meanwhile,by the use of data about gender,age,parameters of the dialyzer,and phosphorus concentration of spent dialysate which was collected after the dialysis for 60 min,a formula was used to calculate phosphorus removal amount of a whole dialysis procedure,and the obtained data were classified as"formula group".Results The total removal amounts of phosphorus,urea nitrogen,creatinine and uric acid in the patent group and traditional group were(27.60±8.39)vs.(27.75±8.45)mmol;(458.15±187.83)vs.(187.83±193.91)mmol;(14 676.46±5 593.39)vs.(5 593.39 ± 5 919.89)μmol;(6 341.61 ± 2 193.88)vs.(6 412.32 ±2 213.69)μmol,respectively.There were no statistically significant differences between the two groups(P>0.05),and the correlation coefficient was 0.996 for all.The total removal amounts of phosphorus in the formula group and traditional group were(32.8±28.03)vs.(27.75±8.45)mmol respectively.There were statistically significant differences between the two groups(t=6.35,P<0.01),and the correlation coefficient r=0.860.Conclusions The new method can perfectly replace the traditional or gold standard method to collect spent dialysate of a whole dialysis procedure.The detected removal amounts of various materials in the samples obtained by this new method are very consistent with those by the traditional method.Furthermore,the new method is significantly superior to the formula method.